Religious and Moral Education: A Panacea for Nation Building in Post-Colonial Ghana - Bansah, C.W. (Department for the Study of Religions, University of Ghana, 2018)
When confronted with the problem of development, most critical thinkers opt for either scientific technology with business in-novations or political expediency. This article expounds on religion as a moral force in national development. As a result of the analysis, it is possible to conclude that religion as a phenomenon does not hamper development, rather, it is the use, and the misuse of religion to push an agenda that projects religion as a tool of aggression, vi-olence and destruction. In a positive tone, the article argues for the use of religious and moral education in political discourse and ho-listic nation building in post-colonial Ghana. The article hinges on Ron Rhodes’ theory of the impossibility of distinguishing evil from good unless one has an infinite reference point which is absolutely good. The rational of the study is therefore to critically examine the impact of religion on the developmental agenda of Ghana, a country in West Africa that is furiously religious and pluralistic. Thus, the study intends to defend religion as the most powerful actor in civil society within the Ghanaian context.
Journal Article
Keywords: Post-Colonialism; Education; Morality; Religion; Socio-Economic Development